A comparative analysis of the abrasion wear characteristics of industrial wastes filled glass/polyester composites based on the design of experiment and neural network. Issue 1 (8th October 2020) - Ray, Subhrajit; Kumar Rout, Arun; Kumar Sahoo, Ashok
Abstract: This article presents the abrasion wear behaviour of different industrial wastes filled glass/polyester composites. Two types of fillers such as fly ash and granite dust are chosen with different weight proportions along with polyester and glass fiber for fabricating the composite using hand layup route. Abrasion wear properties of the developed composites are studied in the dry sand abrasion wear test rig as per the ASTM‐G‐65 standard. The experiments were conducted based on Taguchi design. Between the two fillers, granite filled composite showed better abrasion resistance property as compared with fly ash. Normal load and filler content are found to be the most influential factor for the abrasion loss of the composites followed by abrading distance and sliding velocity. The results are predicted using neural network and also compared with the experimental and regression model data. Abraded surfaces are examined by the SEM to ascertain the different wear mechanisms responsible for abrasion loss of material. Abstract : Fabrication of composite using hand‐lay‐up method.